Affectivity in schizophrenia: Its relations with functioning, quality of life, and social support satisfaction. Issue 7 (18th February 2020) - Pinho, Lara G.; Pereira, Anabela; Chaves, Cláudia; Sequeira, Carlos; Sampaio, Francisco; Correia, Tânia; Gonçalves, Amadeu; Ferré‐Grau, Carme
Abstract: Objective: To evaluate the relationship between affectivity and sociodemographic and clinical characteristics, quality of life, functioning, and social support satisfaction in schizophrenia. Method: Cross‐sectional study of a sample of 282 schizophrenic patients. An interview was performed using a sociodemographic and clinical questionnaire and scales to evaluate positive and negative affect, quality of life, social support satisfaction, and functioning. Results: Participants' employment status, gender, whether they smoked, hospitalization in the last year, antidepressant medication and benzodiazepines, quality of life, functioning, and satisfaction with social support had relationships with positive or negative affect. Conclusion: This study provides further understanding of the factors related to affectivity in schizophrenia. More studies are needed to prove these relations and their effects on rehabilitation in people with schizophrenia.